Expressionism in painting contemporary in Iraq Study features formalism: عبد الرزاق جبار رحيل الكناني (Al-Academy, 2016)
In the present research is marked (expressive drawing in contemporary Iraq, the study of morphological features) eating expressive as the direction of modern art in the drawing for the period before and after World Wars I and II. And follow the tracks. And in research and investigation about the origins and sources and characteristics of expressionist painting at adult patrons and art gatherings, and the extent of their impact in the drawing for contemporary Iraqi sixties and seventies generation (generation of professors) and down to the younger generation in the eighties of the last century. Over the nearly two decades of history of fine movement in Iraq, a period specified in the search within the limits of temporal boundaries, and by analyzing the paintings that were the possession of the Department of Fine Arts in Baghdad, and the sources and photographers and internet sites. From here came the question: Is there a justification for the study of this effect in the (contemporary drawing in Iraq) and morphological features that must be studied? The search consists of four main chapters. Chapter I: general framework for research and began to research the problem and its significance, objectives and definitions of the terms contained therein. The second chapter containing the theoretical framework for the research came Bembages four: the first section root historic expressive, which revolved around the concept of expression in the arts Alchskilleh, and Achkalyate animated in form and substance and content according to the changes in the structures of ideological, intellectual, philosophical, psychological and environmental variable natural and social across times and places mixed. And included a second section, (intellectual foundations of modernity) and eat the philosophical study of the problem of modernity requires that inspired the various analyzes that dealt with to do the pattern of modernity helps us to understand the internal logic, if I may say so to build the ideal style of modernity possible to see that it is this pattern on three basic concepts are (self-, rationality, nihilism), which together constitute the basis of philosophical modernity, and a section on the topic are the three axes (Descartes and subjectivity (f) of Leibniz and rationality) and (Nietzsche and nihilism). The third section (expressive in drawing European modern) and show that the expressive movement and direction of expressing feelings of self more than to express the objective facts, While the expressive coincide with art and Germanic culture, but it is not a phenomenon of Germanic, northeast, but a European, but global in century century. The fourth topic (Expressionism in painting contemporary in Iraq, a study in artistic styles) section dealt generations of Iraqi artists since the fifties and down to the younger generation. The third chapter dealt with research procedures and the research community inventory and analysis of the samples selected in a manner amounting to deliberate acts of three Iraqi artists produced their work during the past within the limits specified in the temporal limits of the search. Find and seal the fourth quarter, indicating the most important findings, conclusions and recommendations and proposals